Manufacturing method of high-strength titanium alloy barrel
By adding Cu powder to TC11 titanium alloy powder and using electron beam selection melting technology to refine the grain, the problem of degradation of the mechanical properties of the thin-wall cylinder of TC11 titanium alloy in the selected laser melting technology is solved, and high strength and good plasticity are achieved.
Patent Information
- Application Number
- CN202411812838.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
AI Technical Summary
Selected laser melting technology When preparing TC11 titanium alloy thin-walled cylinders, the coarse columnar grains caused by degradation of mechanical properties, affecting the service performance of the parts.
By mixing the powder by ball milling and mixing the powder, Cu powder is mixed with TC11 titanium alloy powder to prepare alloying powder, and through electron beam selection melting technology, melting layer by layer to form a titanium alloy cylinder, increasing the supercooling degree of the melt pool component during melting and forming, and refining the grains.
The high strength and good plasticity of the titanium alloy cylinder are achieved, the anisotropy problem caused by coarse columnar grains is solved, and the mechanical properties and service performance of the parts are improved.
Smart Images

Figure CN119703124A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of precision manufacturing, and in particular to a composite manufacturing method for a large-size TC11 titanium alloy thin-walled cylinder. Background Art
[0002] The thin-walled cylinder is a key metal component of aerospace engines, which is subjected to severe flight mechanical loads and thermal loads during engine operation. With the development of aerospace technology, the structure of thin-walled cylinders of aerospace engines has become more and more complex, and the material has evolved from traditional high-strength steel to lightweight high-strength titanium alloys. The traditional process flow of high-strength steel cylinders of engines is: spinning cylinder → assembling welding joints and external components → whole shell quenching and tempering heat treatment → whole shell machining.
[0003] TC11 is an α+β type heat-resistant titanium alloy. Due to its high strength, good corrosion resistance and thermal stability, TC11 titanium alloy cylinder has superior lightweight advantages compared to high-strength steel cylinders. However, TC11 titanium alloy has poor spinnability and machinability, resulting in the forming performance of thin-walled cylinders far inferior to traditional ultra-high-strength steel, which greatly limits the application of titanium alloys in thin-walled cylindrical parts of solid rocket engines.
[0004] Selective laser melting technology is a process in which the laser beam rapidly melts the metal powder according to the CAD graphic data, and "stacks" it layer by layer into various metal parts with complex shapes and a density close to 100%. It has unique advantages in the processing of complex structural parts, variable cross-sections and special-shaped components, and has a series of advantages such as high forming accuracy and high material utilization.
[0005] In recent years, selective laser melting technology has gradually begun to be used in the aerospace field. For example, Patent 202010738832.9 discloses a process method for laser additive manufacturing of high-strength aluminum alloy structures, which can realize the forming of complex parts such as bionic structures and topological optimization structures, and the strength of aluminum alloys can reach more than 530MPa. Patent 202011489777.0 discloses a method for additive manufacturing of complex structures of high-strength aluminum alloys, which reduces the surface roughness of the formed parts by optimizing the selective laser melting forming process.
[0006] The above patents all use selective laser melting technology for direct forming, but the existing selective laser melting equipment is relatively small, with a printing height of less than 1600mm, and cannot achieve integrated printing of parts larger than 2000mm. The composite manufacturing technology that combines selective laser melting additive manufacturing and welding can achieve the forming of large-size parts. In addition, the organizational characteristics of TC11 titanium alloy parts prepared by selective laser melting are coarse columnar grains, which are composed of fine martensitic α phases inside, which are significantly different from the organization of titanium alloy forgings. Such coarse columnar grains usually lead to anisotropy of mechanical properties, affecting the service performance of parts. Summary of the invention
[0007] In order to overcome the disadvantage of reduced mechanical properties caused by coarse columnar grains in manufacturing TC11 titanium alloy thin-walled cylinder by selective laser melting, the present invention proposes a composite manufacturing method for TC11 titanium alloy thin-walled cylinder.
[0008] The specific process of the present invention is:
[0009] Step 1, preparing alloyed powder:
[0010] The Cu powder and the TC11 titanium alloy powder are evenly mixed by ball milling to obtain a mixed powder.
[0011] In the mixed powder, the mass percentage of Cu powder is 1.3% to 2.8%, and the mass percentage of TC11 titanium alloy powder is 98.7% to 97.2%.
[0012] When preparing the mixed powder, the ball mill speed is 300r / min; the ball-to-material ratio is 3:10.
[0013] The TC11 powder is spherical powder with a particle size of 48 to 140 μm. The Cu powder is spherical powder with a particle size of 0.5 to 4 μm.
[0014] Step 2: Create a 3D digital model:
[0015] According to the geometric shape of the high-strength titanium alloy parts to be formed, the three-dimensional model is modeled and designed; the model is input into the slicing software to draw the three-dimensional model of the part, and the three-dimensional model is cut into slices of equal thickness along the height direction to obtain the slice scanning data of the part, and the slice scanning data is imported into the electron beam selective melting device.
[0016] The thickness of each sheet layer is 60 μm.
[0017] Step 3, vacuum:
[0018] The obtained alloyed powder was placed in the powder bin of the electron beam selective melting device, the molding cavity was sealed, and the vacuum degree was drawn to 5.0×10 -4 Pa, and maintain this vacuum degree until the manufacture of the high-strength titanium alloy cylinder is completed.
[0019] The formed substrate is preheated to 680-750°C using an unfocused electron beam.
[0020] Step 4, prepare powder layer:
[0021] The forming substrate is lowered by 60 μm, and the alloyed powder in the powder bin of the electron beam selective melting device is evenly spread on the preheated forming substrate using a scraper to form a powder layer;
[0022] The electron beam is started to scan and preheat the powder layer to obtain a preheated powder layer.
[0023] The thickness of the powder layer is 60 μm.
[0024] During the scanning preheating, the current is 40 mA and the scanning time is 13 to 16 seconds.
[0025] Step 5, scanning and melting of the first layer of molding area:
[0026] According to the slice data, the preheated powder layer is scanned and melted by electron beam, and the molding area after the first layer scanning and melting is obtained.
[0027] When the first layer is scanned and melted, the scanning speed of the electron beam is 1.2-1.5 m / s, the scanning current is 8-9 mA, and the scanning interval is 0.1 mm.
[0028] Step 6, manufacturing of titanium alloy cylinder additive parts:
[0029] The manufacturing of the titanium alloy cylinder additive part refers to completing the scanning melting of the remaining forming areas layer by layer.
[0030] Scanning and melting of the second layer forming area. Specifically:
[0031] Repeat step 4 to evenly spread the alloyed powder in the powder bin of the electron beam selective melting device on the surface of the molding area obtained by the first layer scanning and melting, to form a second layer of powder ply; the thickness of the second layer of powder ply is 60 μm.
[0032] Repeat step 5 to perform selective scanning melting of the second powder layer by electron beam. During the scanning melting, the scanning speed is 1.2-1.5 m / s, the scanning current is 8-9 mA, and the scanning interval is 0.1 mm.
[0033] The molding area melted by the second layer scanning is obtained.
[0034] The scanning and melting of the second layer forming area is repeated until a set height is reached to obtain a semi-finished product of a titanium alloy cylinder additive component.
[0035] The semi-finished product of the titanium alloy cylinder additive part is naturally cooled to below 100° C. under vacuum conditions; and the additive titanium alloy cylinder is obtained after cleaning.
[0036] At this point, the manufacturing of the titanium alloy cylinder additive component is completed.
[0037] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0038] 1. The present invention overcomes the problems of traditional titanium alloy thin-walled cylinder processing, such as many steps, long cycle, low efficiency, and easy deformation and tolerance, and avoids the process problems of traditional titanium alloy forging, spinning, etc. It can realize the integrated forming of cylinder sections and external parts, and does not require welding, heat treatment and other steps. It can directly realize the manufacture of high-strength titanium alloy thin-walled cylinder, and has the characteristics of short processing cycle, high production efficiency, excellent organizational performance, etc.
[0039] 2. The present invention adds Cu powder to TC11 alloy powder by mixed powder alloying, increases the supercooling of the molten pool composition during melting and forming, increases the nucleation rate, thereby refining the grains, and promoting the transformation of columnar grains to equiaxed grains, thereby obtaining excellent mechanical properties, and solving the problems of obvious anisotropy and low plasticity caused by coarse columnar crystals in the TC11 titanium alloy structure prepared by electron beam selective melting. The solute element plays a key role in the supercooling of the titanium alloy composition, and the generation rate of supercooling of the composition is determined by the growth inhibition coefficient Q of the solute. The larger Q is, the faster the alloy can produce supercooling of the composition. In the TC11 alloy, the unit mass growth inhibition coefficient Q0 of the main elements Al and Zr is approximately equal to 0, while the unit mass growth inhibition coefficient of the Cu element is approximately 6.5, that is, adding a certain amount of Cu can cause the TC11 titanium alloy to produce the effect of supercooling of the composition. The TC11 titanium alloy electron beam additive manufacturing specimens prepared by mixed alloying have good strength and plasticity. Their transverse mechanical properties are: tensile strength 1106MPa, yield strength 993MPa, and elongation 13%; their high-direction mechanical properties are: tensile strength 1084MPa, yield strength 959MPa, and elongation 11%. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is the metallographic structure of TC11 titanium alloy prepared by electron beam selective melting.
[0041] Figure 2 This is a SEM photo of the fracture of TC11 titanium alloy tensile specimen prepared by electron beam selective melting.
[0042] Figure 3 This is a photo of the TC11 titanium alloy cylinder prepared by electron beam selective melting.
[0043] Figure 4 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0044] This embodiment is a method for manufacturing a high-strength titanium alloy cylinder.
[0045] The specific process of this embodiment is:
[0046] Step 1, preparing alloyed powder:
[0047] The Cu powder and the TC11 titanium alloy powder are evenly mixed by ball milling to obtain a mixed powder.
[0048] In the mixed powder, the mass percentage of Cu powder is 1.3% to 2.8%, and the mass percentage of TC11 titanium alloy powder is 98.7% to 97.2%.
[0049] The TC11 titanium alloy powder is of prior art, and has an Al content of 5.8-7.0%, a Zr content of 0.8-2.0%, a Si content of 0.20-0.35%, and a Fe content of ≤0.25%, a C content of ≤0.10, a N content of ≤0.05, a H content of ≤0.012, and an O content of ≤0.15; the percentages are mass percentages.
[0050] The TC11 powder is spherical powder with a particle size of 48 to 140 μm. The Cu powder is also spherical powder with a particle size of 0.5 to 4 μm.
[0051] The ball milling method is used to make the Cu powder fully adhere to the TC11 titanium alloy powder to achieve uniform mixing of the powders. The speed of the ball mill is 300r / min; the ball-to-material ratio is 3:10.
[0052] A uniformly mixed alloyed powder is obtained.
[0053] Process parameters of step 2 of each embodiment
[0054]
[0055]
[0056] Step 2: Create a 3D digital model:
[0057] According to the geometric shape of the high-strength titanium alloy parts to be formed, the three-dimensional model is modeled and designed; the model is input into the slicing software to draw the three-dimensional model of the part, and the three-dimensional model is cut into slices of equal thickness along the height direction to obtain the slice scanning data of the part, and the slice scanning data is imported into the electron beam selective melting device.
[0058] The thickness of each sheet layer is 60 μm.
[0059] Step 3, vacuum:
[0060] The obtained alloyed powder was placed in the powder bin of the electron beam selective melting device, the molding cavity was sealed, and the vacuum degree was drawn to 5.0×10 -4 Pa, and maintain this vacuum degree until the manufacture of the high-strength titanium alloy cylinder is completed.
[0061] The formed substrate is preheated to 680-750°C using an unfocused electron beam.
[0062]
[0063] Step 4, prepare powder layer:
[0064] The forming substrate is lowered by 60 μm, and the alloyed powder placed in the powder bin of the electron beam selective melting device is evenly spread on the preheated forming substrate using a scraper to form a powder layer; the thickness of the powder layer is 60 μm.
[0065] The electron beam is started to scan and preheat the powder layer; during the scanning and preheating, the current is 40 mA and the scanning time is 13 to 16 seconds to obtain a preheated powder layer.
[0066]
[0067] Step 5, scanning and melting of the first layer of molding area:
[0068] According to the slice data, the preheated powder layer is subjected to selective scanning melting by electron beam. During the scanning melting, the scanning speed is 1.2-1.5 m / s, the scanning current is 8-9 mA, and the scanning interval is 0.1 mm.
[0069] The molding area melted by the first layer scan is obtained.
[0070] Process parameters of step 3 of each embodiment
[0071]
[0072] Step 6, manufacturing of titanium alloy cylinder additive parts:
[0073] The manufacturing of the titanium alloy cylinder additive part refers to completing the scanning melting of the remaining forming areas layer by layer.
[0074] Scanning and melting of the second layer forming area. Specifically:
[0075] Repeat step 4 to evenly spread the alloyed powder in the powder bin of the electron beam selective melting device on the surface of the molding area obtained by the first layer scanning and melting, to form a second layer of powder ply; the thickness of the second layer of powder ply is 60 μm.
[0076] Repeat step 5 to perform selective scanning melting of the second powder layer by electron beam. During the scanning melting, the scanning speed is 1.2-1.5 m / s, the scanning current is 8-9 mA, and the scanning interval is 0.1 mm.
[0077] The molding area melted by the second layer scanning is obtained.
[0078] The scanning and melting of the second layer forming area is repeated until a set height is reached to obtain a semi-finished product of a titanium alloy cylinder additive component.
[0079] The semi-finished product of the titanium alloy cylinder additive part is naturally cooled to below 100° C. under vacuum conditions; and the additive titanium alloy cylinder is obtained after cleaning.
[0080] At this point, the manufacturing of the titanium alloy cylinder additive component is completed.
Claims
1. A method for manufacturing a high-strength titanium alloy cylinder, characterized in that: The specific process is: Step 1, preparing alloyed powder: The Cu powder and the TC11 titanium alloy powder are evenly mixed by ball milling to obtain a mixed powder; Step 2: Create a 3D digital model: The geometric shape of the formed high-strength titanium alloy parts is used to carry out the modeling and design of the three-dimensional model; the model is input into the slicing software to draw the three-dimensional model of the part, and the three-dimensional model is cut into slices of equal thickness along the height direction to obtain the slice scanning data of the part, and the slice scanning data is imported into the electron beam selective melting device; Step 3, vacuuming: The obtained alloyed powder was placed in the powder bin of the electron beam selective melting device, the molding cavity was sealed, and the vacuum degree was drawn to 5.0×10 -4 Pa, and maintain the vacuum degree until the manufacture of the high-strength titanium alloy cylinder is completed; The formed substrate is preheated to 680-750°C using an unfocused electron beam; Step 4, prepare powder layer: The forming substrate is lowered by 60 μm, and the alloyed powder in the powder bin of the electron beam selective melting device is evenly spread on the preheated forming substrate using a scraper to form a powder layer; Starting the electron beam to scan and preheat the powder layer to obtain a preheated powder layer; Step 5, scanning and melting of the first layer of molding area: According to the slice data, the preheated powder layer is selectively scanned and melted by electron beam; The first layer scans the melted forming area; Step 6, manufacturing of titanium alloy cylinder additive parts: The manufacturing of the titanium alloy cylinder additive part refers to completing the scanning melting of the remaining forming areas layer by layer; Scanning melting of the second layer forming area; specifically: Repeat step 4 to evenly spread the alloyed powder in the powder bin of the electron beam selective melting device on the surface of the molding area obtained by the first layer scanning and melting, to form a second layer of powder ply; the thickness of the second layer of powder ply is 60 μm; Repeat step 5 to perform selective scanning melting of the second powder layer by electron beam; during the scanning melting, the scanning speed is 1.2-1.5 m / s, the scanning current is 8-9 mA, and the scanning interval is 0.1 mm; The molding area melted by the second layer scanning is obtained; Repeat the scanning and melting of the second layer forming area until the set height is reached to obtain a semi-finished product of the titanium alloy cylinder additive component; The semi-finished product of the titanium alloy cylinder additive part is naturally cooled to below 100° C. under vacuum conditions; and the additive titanium alloy cylinder is obtained after cleaning; At this point, the manufacturing of the titanium alloy cylinder additive component is completed.
2. The method for manufacturing a high-strength titanium alloy cylinder according to claim 1, characterized in that: In the mixed powder, the mass percentage of Cu powder is 1.3% to 2.8%, and the mass percentage of TC11 titanium alloy powder is 98.7% to 97.2%.
3. The method for manufacturing a high-strength titanium alloy cylinder according to claim 1, characterized in that: When preparing the mixed powder, the ball mill speed is 300r / min; the ball-to-material ratio is 3:
10.
4. The method for manufacturing a high-strength titanium alloy cylinder according to claim 1, characterized in that: The TC11 powder is spherical powder with a particle size of 48 to 140 μm; the Cu powder is spherical powder with a particle size of 0.5 to 4 μm.
5. The method for manufacturing a high-strength titanium alloy cylinder according to claim 1, characterized in that: The thickness of each sheet layer is 60 μm.
6. The method for manufacturing a high-strength titanium alloy cylinder according to claim 1, characterized in that: The thickness of the powder layer is 60 μm.
7. The method for manufacturing a high-strength titanium alloy cylinder according to claim 1, characterized in that: During the scanning preheating, the current is 40 mA and the scanning time is 13 to 16 seconds.
8. The method for manufacturing a high-strength titanium alloy cylinder according to claim 1, characterized in that: When the first layer is scanned and melted, the scanning speed of the electron beam is 1.2-1.5 m / s, the scanning current is 8-9 mA, and the scanning interval is 0.1 mm.
Citation Information
Patent Citations
Technological process for laser additive manufacturing of high-strength aluminum alloy structure
CN112077305A
High-strength aluminum alloy complex component additive manufacturing method
CN112621572A
Ion slow-release high-strength Ti-Cu alloy and 3D printing method and application thereof
CN114457258A
Method for improving strength of additive manufacturing titanium alloy
CN116555612A
Titanium alloy structure regulation and control method for high-power laser melting deposition
CN117340267A
Cited By
Manufacturing method of aluminum alloy conical metal piece
CN120516356A
Aircraft cylinder section and additive manufacturing method thereof
CN121084655A